Stability and physical compatibility of parenteral nalbuphine hydrochloride during continuous infusion in pediatrics - Romain Paoli-Lombardo; Vincent Arcani; Delphine Dazan; Caroline Castera-Ducros; Marie-Anne Esteve; Marjorie Roudot; Chloé Wanert; Caroline Ovaert; Christophe Curti; Patrice Vanelle; Pascal Rathelot (PLoS ONE, 2025)
In pediatric practice, nalbuphine hydrochloride can be administered by continuous infusion through a multiport manifold or Y-site connection over 24 h in a 60 mL polypropylene syringe unprotected from light at concentrations ranging from 52.1 µg.mL-1 to 333.3 µg.mL-1 in normal saline (NS). To limit the need for multiple injections, nalbuphine hydrochloride may be co-administered with other drugs. Its stability and compatibility were already studied at concentration ranges equal or higher than 1.0 mg.mL-1. However, when nalbuphine hydrochloride needs to be diluted for a pediatric administration its stability in NS over 24 h of light exposure at ambient temperature and its compatibility with other drugs have never been studied before. A novel chromatographic method using high-performance liquid chromatography (HPLC) was validated by the International Council for Harmonisation (ICH) Q2 (R1) guidelines. The stability of nalbuphine hydrochloride and the appearance of degradation products under five experimental conditions (light, heat, oxidation, basicity, and acidity) were monitored by HPLC-UV for 24 h at ambient temperature at three concentrations administered in pediatric departments (52.1 µg.mL-1, 166.7 µg.mL-1 and 333.3 µg.mL-1). The physical compatibility of nalbuphine hydrochloride with 1:1 (v/v) mixtures of selected drugs used in pediatrics was evaluated by visual inspection and with a 10 µm and 25 µm sub-visible particle counter. Our nalbuphine hydrochloride quantification method has been validated and was stability-indicating. The stability of nalbuphine hydrochloride and the forced degradation assay (light, heat, oxidation, basicity, and acidity) studied for the three concentrations of nalbuphine hydrochloride diluted in 48 mL of NS and stored in a 60 mL polypropylene syringe unprotected from light were compliant for at least 24 h at ambient temperature. Nalbuphine hydrochloride in NS was found to be compatible with several drugs, but was incompatible with furosemide and amphotericin B. Nalbuphine hydrochloride can be administered in pediatric practice using a syringe pump for 24 h. However, drug-drug incompatibilities need to be considered when it is administered through a multiport manifold or Y-site connection.